G-CSF maintains controlled neutrophil mobilization during acute inflammation by negatively regulating CXCR2 signaling - Besnik Bajrami (2018)
© 2016 Bajrami et al. Cytokine-induced neutrophil mobilization from the bone marrow to circulation is a critical event in acute inflammation, but how it is accurately controlled remains poorly understood. In this study, we report that CXCR2 ligands are responsible for rapid neutrophil mobilization during early-stage acute inflammation. Nevertheless, although serum CXCR2 ligand concentrations increased during inflammation, neutrophil mobilization slowed after an initial acute fast phase, suggesting a suppression of neutrophil response to CXCR2 ligands after the acute phase. We demonstrate that granulocyte colony-stimulating factor (G-CSF), usually considered a prototypical neutrophil-mobilizing cytokine, was expressed later in the acute inflammatory response and unexpectedly impeded CXCR2-induced neutrophil mobilization by negatively regulating CXCR2-mediated intracellular signaling. Blocking G-CSF in vivo paradoxically elevated peripheral blood neutrophil counts in mice injected intraperitoneally with Escherichia coli and sequestered large numbers of neutrophils in the lungs, leading to sterile pulmonary inflammation. In a lipopolysaccharide-induced acute lung injury model, the homeostatic imbalance caused by G-CSF blockade enhanced neutrophil accumulation, edema, and inflammation in the lungs and ultimately led to significant lung damage. Thus, physiologically produced G-CSF not only acts as a neutrophil mobilizer at the relatively late stage of acute inflammation, but also prevents exaggerated neutrophil mobilization and the associated inflammation-induced tissue damage during early-phase infection and inflammation.